Power strategy in DC/DC converters to increase efficiency of electrical stimulators - Pablo Aqueveque; Vicente Acuña; Francisco Saavedra; Adrien Debelle; Laurent Lonys; Nicolas Julémont; François Huberland; Carmen Godfraind; Antoine Nonclercq (PAGEPress Publications, 2016)
Power efficiency is critical for electrical stimulators. Battery life of wearable stimulators and wireless power transmission in implanted systems are common limiting factors. Boost DC/DC converters are typically needed to increase the supply voltage of the output stage. Traditionally, boost DC/DC converters are used with fast control to regulate the supply voltage of the output. However, since stimulators are acting as current sources, such voltage regulation is not needed. Banking on this, this paper presents a DC/DC conversion strategy aiming to increase power efficiency. It compares, in terms of efficiency, the traditional use of boost converters to two alternatives that could be implemented in future hardware designs.